2015
DOI: 10.1177/0148607115579939
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors for Developing Catheter‐Related Bloodstream Infection in Home Parenteral Nutrition Patients

Abstract: Using the PICC, 1 additional infusion day per week decreased the time to first CRBSI, while having the Hickman catheter managed by a home care nurse increased the mean CRBSI incidence. No other risk factors were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…In addition to Cotogni et al, 7 3 other studies compared CLABSI rates in tunneled vs PICC CVADs. 11,13,14 Christenson and associates and Bech and associates appeared to analyze the same dataset of Danish HPN patients, and while different questions were asked, similar results were found. Christensen et al 14 reported higher CLABSI rates for PICC compared with tunneled CVADs and a shorter time to first infection (84 ± 94 days vs 297 ± 387 days; P < .05).…”
Section: Question 1: Does the Type Of Cvad (Tunneled Implanted Or Pmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition to Cotogni et al, 7 3 other studies compared CLABSI rates in tunneled vs PICC CVADs. 11,13,14 Christenson and associates and Bech and associates appeared to analyze the same dataset of Danish HPN patients, and while different questions were asked, similar results were found. Christensen et al 14 reported higher CLABSI rates for PICC compared with tunneled CVADs and a shorter time to first infection (84 ± 94 days vs 297 ± 387 days; P < .05).…”
Section: Question 1: Does the Type Of Cvad (Tunneled Implanted Or Pmentioning
confidence: 58%
“…In addition to Cotogni et al, 3 other studies compared CLABSI rates in tunneled vs PICC CVADs . Christenson and associates and Bech and associates appeared to analyze the same dataset of Danish HPN patients, and while different questions were asked, similar results were found.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The incidence of catheter-related bloodstream infections (CRBSI) with PICCs varied among different studies and ranged from 0 to 1.63 per 1000 catheter days. 4,5,17,[22][23][24]31,34,38 In the study by Cotogni et al, 5 CRBSI rate was significantly lower with PICCs compared to CICCs (0 vs. 0.87 per 1000 catheter days, P < 0.01), and in the study by Botella-Carretero et al, 17 only PICCs, but not CICCs, showed lower CRBSI incidence than with implanted ports (P = 0.043). However, a higher CRBSI rate and a lower time to first CRBSI were reported for PICCs versus CICCs in a 6-year follow-up study in HPN patients (1.43 ± 0.20 vs. 0.95 ± 0.39 per 1000 catheter days, 83.91 ± 93.75 vs. 297.21 ± 386.91 days, P < 0.001).…”
Section: Safety Outcomesmentioning
confidence: 91%
“…The reported mean catheter dwell time/duration ranged from 9.4 to 127 days with PICCs 6,10-12,15,16,18,22-35 versus 4.4 to 7.3 days with PIVCs 6,10 and 6.83 to 324.92 days with CICCs. 6,11,16,22,28,33 In 2 studies, mean catheter dwell time was significantly higher for PICCs versus CICCs (P < 0.0001), 11,16 whereas the opposite was true in 2 other studies (P < 0.001). 22,33 In the study by Periard et al 10 in patients requiring IV therapy for at least 5 days, mean catheter dwell time was significantly higher for PICCs compared to PIVCs (9.4 vs. 7.3 days, P = 0.01).…”
Section: Efficacy Outcomesmentioning
confidence: 95%